2004
DOI: 10.1590/s1678-97412004000100010
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<b>Effects of the pleural drain site on the pulmonary function after coronary artery bypass graf</b>]]>

Abstract: Objective: To analyze pulmonary functional changes and pain in patients undergoing off-pump coronary artery bypass grafting utilizing a left internal thoracic artery graft, comparing pleural drain insertion through the intercostal space and the subxyphoid approach.Methods: Twenty-eight patients (mean age 57.4 ± ± ± ± ± 8.4 years) were divided into two groups, according to the pleural drain site. Group LI (n=15) had the pleural drain inserted through the sixth left intercostal space at the mid-axillary line and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 14 publications
4
19
0
7
Order By: Relevance
“…In our study, the tube was placed under direct vision before chest closure, ensuring the proper positioning. Analyzing the painful effects, Guizilini states that intercostal chest tube placement increases postoperative pain, with restriction of deep breathing, coughing, and changing patient's position on the bed 10 , findings that are consistent with our results.…”
Section: Momentsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the tube was placed under direct vision before chest closure, ensuring the proper positioning. Analyzing the painful effects, Guizilini states that intercostal chest tube placement increases postoperative pain, with restriction of deep breathing, coughing, and changing patient's position on the bed 10 , findings that are consistent with our results.…”
Section: Momentsupporting
confidence: 91%
“…Guizilini et al 10 conducted a similar study, but in patients without CPB, and found results similar to ours, although they did not study the immediate effect of chest tube removal 10 .…”
Section: Momentsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, contemporary evidence suggests that shifting the site of pleural drain insertion to the subxyphoid position minimizes chest wall trauma and preserves respiratory function in the early postoperative period [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…The insertion of an intercostal pleural drain causes additional injury to the thorax, as it becomes necessary to perforate intercostal muscles and the parietal pleura, which also interferes with respiratory movements. Consequently, the location of the pleural drain might have an influence on the discomfort suffered by the patient and on the degree of alteration of pulmonary function 5. Previous studies have examined the efficiency of pleural drainage with different methods, such as daily chest x-rays (CXRs),57 thoracic ultrasonography (USG)7 and echocardiography (ECHO);48 however, no study has demonstrated reliably that any means of pleural drainage is superior.…”
mentioning
confidence: 99%